Analysis of the Influence of Spiritual Leadership, Work Motivation, and Non-Physical Work Environment on the Performance of Regional Office Employees of the Ministry of Religion, Maluku Province - Wismono, Pujo; Leiwaherilla, Novalien Carolin; Pentury, G.M (Jurnal Ekonomi, 2024)
This research is based on the influence of leadership which aims to test and analyze the influence of spiritual leadership, work motivation and non-physical work environment on the performance of regional office employees of the Ministry of Religion of Maluku Province. This research is causal associative research. which is intended to reveal problems that are causal relationships between two or more variables. In this research there are independent variables (which influence) and dependent variables (which are influenced). This research only discusses the influence of Leadership, Motivation, Work Environment on this research which has been determined, so this type of research is quantitative research.spiritual leadership on the performance of employees of the Maluku Province Regional Office of Religion. The spiritual leadership variable has a calculated t value of 4.563. This value is greater than the t table. In addition, the Sig value is 0.000 < 0.05. Based on the results of statistical tests, spiritual leadership has a significant influence on the performance of employees of the Maluku Province Religious Regional Office, so Hypothesis 1 «It is suspected that there is a partial influence of spiritual leadership on the performance of employees of the Maluku Province Religious Regional Office» is empirically accepted and proven in this research. Also in line with Silalahi and Lubis' research, they conducted research entitled the influence of spiritual leadership on employee performance through Islamic spirituality. With the research results, leaders with good spirituality who form Islamic spirituality in the workplace improve the performance of lecturers and staff. The application of this research will be carried out at Medan City Universities. In addition, the Sig value is 0.002 < 0.05. Based on the results of statistical tests, work motivation has a positive and significant influence on the performance of employees at the Religious Regional Office of Maluku Province, thus Hypothesis 2 «It is suspected that there is a partial influence between work motivation on the performance of employees at the Religious Regional Office of Maluku Province» is accepted. empirical and proven in this research. Yogyakarta in 2021, numbering 140.